Forensic psychological expertise: Aspects of legal and psychological adjustment - Justickis, Viktoras; Valickas, Gintautas (Psichologija, 2003)
The first part of the article deals with legal position of psychologist-expert in criminal, civil and administrative procedure. The aim, tasks and functions of the forensic psychological expertise and psychologist- expert’s duties and rights are analyzed. The second part is devoted to special branches of psychological expertise: a) assessment of people with reduced liability; b) assessment of offender’s states in a crime situation as well as sudden great emotional arousal; c) assessment of a person’s ability to take part in criminal procedure; d) assessment of parts ability to give testimonies; e) assessment of a suspect’s and accused person’s ability to understand and use his right to refuse giving testimonies; f) assessment of a person’s capability in civil procedure. In the third part of the article are analyzed requirements of professional ethics as well as the main ethical dilemmas, which can meet forensic psychologist (confidentiality, roles and emotional conflicts, impartiality).